Implications of students’ dominant intelligence on classroom interaction / Isyati Suparman - Suparman, Isyati (Akademi Pengajian Bahasa, 2021)
Language is acquired subconsciously while interacting with people, thus interaction is crucial in any language learning classroom as it is the means to promote language acquisition among students. However, in reality, interactions in the classroom do not happen much and students tend to remain passive and not taking part in discussions. Previous research has shown that there are few reasons that influence students’ interactions in the classroom. Their reluctance to participate could be due to language anxiety and self-confidence which involves internal or psychological factors. The purpose of this paper is to review an internal factor (Dominant Intelligence) which may have influence on students’ language anxiety. This paper shall discuss Dominant Intelligence as the dominating ability that one possesses and how it may help reduce students’ language anxiety and thus enhance their interaction in the classroom.